Effectiveness of Neuromuscular Taping on Balance, Proprioception, Pain, and Nerve Conduction Parameters in Patients with Diabetic Peripheral Neuropathy: A Two-Group Pretest–Posttest Randomized Sham-Controlled Trial: A Pilot Study - Kanika Thakur; Manu Goyal (Journal of Diabetology)
Aim: Neuromuscular Taping (NMT) is the application of elastic adhesive tape to the skin without any tension in it. NMT creates wrinkles on the surface of the skin to help stretch the skin passively and this elongation force assists in muscle contraction and relaxation. Therefore, this study aimed to assess the effectiveness of NMT in the improvement of sensorimotor complications following diabetic peripheral neuropathy (DPN).